2015
DOI: 10.1007/s10151-015-1283-8
|View full text |Cite
|
Sign up to set email alerts
|

Robotic transanal surgery for local excision of rectal neoplasia, transanal total mesorectal excision, and repair of complex fistulae: clinical experience with the first 18 cases at a single institution

Abstract: Robotic transanal surgery for local excision, transanal total mesorectal excision, and repair of fistulae is feasible, although these new approaches represent a work-in-progress. Improvement in platform design will likely facilitate the ability to perform more complex procedures. Further research with robotic transanal approaches is necessary to determine whether or not this approach can provide patients with significant benefit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
45
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 49 publications
0
45
0
Order By: Relevance
“…6 A word of caution on the effects of the pneumorectum, as this has been described to cause a pneumodissection along soft tissues in a robotic taTME resulting in abdominal distension with need for conversion. 37 The authors hypothesized this to be the effect of prolonged operative time.…”
Section: Safety Improvementsmentioning
confidence: 99%
“…6 A word of caution on the effects of the pneumorectum, as this has been described to cause a pneumodissection along soft tissues in a robotic taTME resulting in abdominal distension with need for conversion. 37 The authors hypothesized this to be the effect of prolonged operative time.…”
Section: Safety Improvementsmentioning
confidence: 99%
“…The same authors that introduced TAMIS went on to describe the use of a robotic platform for TAMIS in a cadaveric model in 2011, 20 and then extended that robotic TAMIS platform to live patients in 2012. 21 Since then, it has been described in humans using both the GelPOINT Path platform (Applied Medical, Inc.) 22 and a glove port (►Fig. 2).…”
Section: Robotic Transanal Minimally Invasive Surgerymentioning
confidence: 99%
“…Robotic‐TAMIS, first described by Attalah et al and Hompes et al has been the natural progression of laparoscopic‐TAMIS and has been shown to be successful in performing oncologic resection of low and middle rectal tumors . While the current guidelines for LE limit TAE of early rectal neoplasia to within 8 cm of the anal verge, this analysis reports the TAE of 10 rectal lesions of mixed pathology with negative margins using robotic assisted micro surgery with an average distance of 11.1 cm from the anal verge…”
Section: Introductionmentioning
confidence: 98%